Сталий розвиток України: можливості та загрози - Глущенко, Ольга Вікторівна (Київ : ТОВ «ФІНТЕХАЛЬЯНС», 2017)
У статті досліджено можливості та загрози, що виникають у зв’язку переходом України на шлях сталого розвитку. Проведено аналіз показників сталого розвитку України з аналогічними показниками країн компаративної групи. У процесі дослідження доведена гіпотеза про можливість застосування методологічного підходу «за межами ВВП» для оцінки сталого розвитку. Встановлено існування залежності між індексом економічної свободи та показником чутливості до корупції. Описано профіль України у показниках сталого розвитку. Визначені можливості та загрози, що супроводжуватимуть перехід до сталого розвитку України. Встановлено, що Україна має значний інноваційний потенціал, який можливо реалізувати. Основні загрози становлять зростання інтенсивності конфліктів, зменшення чутливості до корупції та державна нестабільність.

The article explores the opportunities and threats that arise in connection with the transition of Ukraine to sustainable development. A comparative analysis of the indicators of sustainable development of Ukraine with similar indicators of the countries in the comparative group is carried out. There have been selected countries meeting a number of common requirements, namely Latvia, Lithuania, Estonia, Georgia and Moldova. The study has proved the hypothesis of applying the Beyond GDP methodological approach to assessing sustainable development. There is a relationship between the index of economic freedom and the indicator of corruption perception due to the fact that the existence of administrative barriers reduces economic freedom and increases tolerance to corruption in the society. There have been analyzed the components of life quality and life safety and described the profile of Ukraine with the indicators of sustainable development. The opportunities and threats that will accompany the transition to sustainable development of Ukraine have been identified. Ukraine has significant innovative and economic potential to achieve. The main threats are increasing the intensity of conflicts, reducing corruption perception, increasing state fragility and state instability.
Sustainable development of Ukraine : opportunities and threats
Keywords: сталий розвиток; за межами ВВП; чутливість до корупції; економічна свобода; державна нестабільність; інновації; індекс сталого розвитку; beyond GDP; corruption perception; economic freedom; innovations; index of sustainable development; state fragility; sustainable development; SOCIAL SCIENCES::Business and economics::Economics